Performance criteria based comparative analysis of indoor localization technologies [Iç Mekan Yer Tespiti Teknolojilerinin Performans Kriterlerine Göre Kaŗsiląstirmali Analizi] - (:unkn) unknown (Institute of Electrical and Electronics Engineers Inc., 2018)
Since the 20th century, location-based systems have become increasingly widespread due to technological advancements. In this respect, developments have been made in the 20th century to ensure that outdoor locational information can be obtained accurately and precisely. In recent years, GPS systems are widely used for outdoor localization. With the increasing use of smartphones and wireless systems in recent years, indoor locational information has become increasingly crucial. The methods used for outdoor location can not be used for indoor locational applications due to some limitations. In this paper, we review and compare commonly used technologies for indoor localization applications. © 2018 IEEE.
Keywords: Bluetooth; Indoor localization; LoRa; RFID; Sigfox; US; UWB; WiFi